Rekonstruksi Pemahaman Riba dalam Hadis (Telaah Historis dan Komparatifatas Interpretasi Ulama Klasik dan Kontemporer) - Hidayat Hidayat; Paisal Paisal; Saru Reza (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to reconstruct the meaning of usury in the hadith to ensure its relevance to modern economic developments by comparing the views of classical and contemporary scholars. Usury is an important concept in Islamic economic law, expressly prohibited in the Qur'an and hadith. However, the emergence of modern banking systems and financial instruments has given rise to differing interpretations regarding the application of usury laws, particularly regarding bank interest. The study employed library research with a qualitative-descriptive approach. The results indicate that classical scholars tended to understand usury textually and applied analogy to transactions mentioned in the hadith. In contrast, contemporary scholars developed a more contextual approach, taking into account changes in the economic system and the needs of modern society. Despite differences in the application of the law to bank interest, both groups of scholars agree that the primary purpose of the prohibition of usury is to prevent exploitation, injustice, and economic oppression. Therefore, a reconstruction of the understanding of usury is necessary to maintain sharia principles and address contemporary economic challenges